Prominent electronic and geometric modifications of palladium nanoparticles by polymer stabilizers for hydrogen production under ambient conditions. - Jones, S; Qu, J; Tedsree, K; Gong, X; Tsang, S (2012)
A remarkable effect from the modification of electronic and geometric properties of Pd nanoparticles by the use of polymer pendant groups bound to the surface of palladium nanoparticles is reported. The degree of electron promotion to the Pd nanoparticles under ambient conditions was found to be dependent on the availability of the lone pair electrons of the pendant groups.